2020
DOI: 10.14235/bas.galenos.2019.3076
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Plantar Pressure Distribution in Overweight and Obese Individuals

Abstract: ÖZ ABSTRACTAmaç: Aşırı kilolu/obez bireylerde ortopedik ayak hastalıkları insidansı ve prevelansındaki artış, bu bireylerin plantar basınç dağılımındaki değişiklikler ile ilişkili olabilir. Bu nedenle, bu çalışmanın amacı, aşırı kilolu/obez bireylerde plantar basınç dağılımının araştırılmasıdır.Yöntemler: Bu çalışma 19-62 yaş aralığında 94 sağlıklı bireyin katılımı ile gerçekleşti. Bireyler vücut kütle indekslerine (VKİ) göre normal kilolu (18,5 kg/m 2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Furthermore, you can see twenty women (11.7%) who had a BMI over 35% in the age group (40-49) years. Besides, there were a similar number of obese women; eight women (0.4%) in the age groups (30-39 years) and ( 50 and only five women (0.2%) in the older age group (60-69) years [9]. Table 2 and figure2 declare the relation of three selected variables relative to age groups (years)(N=170).…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, you can see twenty women (11.7%) who had a BMI over 35% in the age group (40-49) years. Besides, there were a similar number of obese women; eight women (0.4%) in the age groups (30-39 years) and ( 50 and only five women (0.2%) in the older age group (60-69) years [9]. Table 2 and figure2 declare the relation of three selected variables relative to age groups (years)(N=170).…”
Section: Discussionmentioning
confidence: 81%
“…In summary, while our study found no significant prevalence of plantar fasciitis among nurses based on the scoring scale, there was a notable association with the use of high-heeled shoes, indicating a potential risk factor. These findings underscore the importance of ergonomic considerations in nursing footwear to mitigate the risk of plantar fasciitis and enhance the overall well-being of nursing professionals (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 86%
“…The Visual Analogue Scale (VAS) and the Plantar Fasciitis Pain and Disability Scale (PFPS) were utilized to assess pain intensity and disability. The VAS measured pain on a scale of 0 to 100 points, with cut-off points for pain intensity classified as no pain (0-4 mm), mild pain (5-44 mm), moderate pain (45-74 mm), and severe pain (75-100 mm) (7). A PFPS score greater than 35 points indicated significant heel pain due to plantar fasciitis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants declared that the right limb was the dominant limb, and no prior lower limb injuries or abnormities that may affect normal walking and standing. In addition, since BMI and foot arches have important effects on the plantar pressure, so the inclusion criteria for participants also required they had normal weights with BMI < 25 kg/m 2 14 and normal arch feet with arch index falling inside (0.2, 0.28). 15 After signing written informed consents, The experiments were conducted in a research laboratory belonging to College of Automation of NJUPT.…”
Section: Methodsmentioning
confidence: 99%